2016
DOI: 10.1186/s12885-016-2735-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT-1 modulates metastatic potential of tongue squamous cell carcinomas partially through the regulation of small proline rich proteins

Abstract: BackgroundWe previously described several abnormally expressed long non-coding RNA (lncRNA) in tong squamous cell carcinomas (TSCCs) that might be associated with tumor progression. In the present study, we aimed to investigate the role of abnormally expressed metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1) lncRNA in the metastatic potential of TSCC cells and its molecular mechanisms.MethodsExpression levels of MALAT-1 lncRNA were examined via quantitative reverse transcriptase polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 28 publications
1
65
0
1
Order By: Relevance
“…The MALAT1 gene is highly conserved across mammals, suggesting that it may have important biological implications [9]. Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20].…”
Section: Discussionmentioning
confidence: 99%
“…The MALAT1 gene is highly conserved across mammals, suggesting that it may have important biological implications [9]. Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the first identified cancer‐associated lncRNAs, MALAT1 was reported to be overexpressed in gastric cancer (Chen, Liu, Wang et al, 2017), breast cancer (Arun et al, ), prostate cancer (Ren et al, ), cervical cancer (Sun, Qin et al, ), acute myeloid leukemia (Chen, Nagel et al, 2018), medullary thyroid cancer (Chu, Hardin, Schneider, Chen, & Lloyd, ), choriocarcinoma (Shi, Wang, & Yin, ), gallbladder cancer (Sun et al, ), pancreatic cancer (Xie et al, 2017), multiple myeloma (Liu, Wang et al, ), ovarian cancer (Wu et al, 2017), T and natural killer cell lymphoma (Kim, Kim, Yang, Kim, & Yoon, ), acute monocytic leukemia (Huang, Liu et al, ), endometrial stromal sarcoma (Yamada et al, ), myeloma (Cho et al, ), clear cell renal cell carcinoma (Zhang, Yang, Chen, Che, & Zheng, ), esophageal squamous cell carcinoma (Hu et al, ), glioma (Ma, Wang, Li et al, ), osteosarcoma (Cai et al, ), neuroblastoma (Tee et al, ), tongue squamous cell carcinomas (Fang et al, ), hilar cholangiocarcinoma (Tan, Huang, & Li, ), mantle cell lymphoma (Wang, Zhu et al, ), and other tumor tissues. It has been reported that MALAT1 is involved in the regulation of tumor proliferation, apoptosis, invasion, metastasis, and angiogenesis.…”
Section: Physiopathological Role Of Malat1mentioning
confidence: 99%
“…The expression of MALAT1 has been addressed by six studies finding a significant overexpression in four of these. Three studies addressing TSCC (overall 159 patients) found significant overexpression (Fang et al., , ; Liang, Liang, Ouyang, Li, & Yi, ). When dealing with OSCC, two studies with similar sample size showed contrasting results, as only one was able to find significant DE (Arunkumar, Deva Magendhra Rao et al., ; Zhou et al., ).…”
Section: Introductionmentioning
confidence: 99%